Correction: Xing et al. Enhancing the Stability of Litsea Cubeba Essential Oil Emulsions Through Glycosylation of Fish Skin Gelatin via Dry Maillard Reaction. Foods 2024, 13, 3847 - Naiwen Xing; Shikang Tang; Xuejiao Wang; Chaofan Guo; Xiaosong Hu; Junjie Yi (Foods)
Error in Figure [...]